ANALISIS PENGEMBANGAN AGROWISATA JOLLONG DI DESA SITILUHUR, KECAMATAN GEMBONG, KABUPATEN PATI - Agung Indriatno, Danang; Nurcahyanto, Herbasuki; Marom, Aufarul (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
Agrowisata Jollong is an agrotourism located in Sitiluhur Village, Gembong District, Pati Regency. This research aims to analyze the development of Agrowisata Jollong and identify supporting and inhibiting factors for the development of Agrowisata Jollong in Sitiluhur Village, Gembong District, Pati Regency. The research method uses a qualitative descriptive method with data collection techniques through observation, interviews and documentation. Data analysis techniques were carried out using data reduction techniques, data presentation and drawing conclusions. The sampling technique uses purposive sampling technique and data validity is taken through source triangulation. The research results show that there are still problems facing Agrowisata Jollong, especially the phenomena of accessibility (aksesibilitas) and amenities (fasilitas penunjang). Factors inhibiting the development of Agrowisata Jollong can be seen from complaints by Agrowisata Jollong tourists, the topography of Agrowisata Jollong which is in the highlands, and the lack of socialization regarding Agrowisata Jollong entrance tickets. Suggestions that researchers can convey include the need for communication between Agrowisata Jollong with Dinporapar Kabupaten Pati and Dishub Kabupaten Pati, improving the quality of toilets at Agrowisata Jollong, adding disaster evacuation facilities, further socializing entry tickets for Agrowisata Jollong.